Neosystemic curricular metatheory and challenges in education research - Tapiero Vásquez, Elías (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Based on the execution of a program and a research line from which it emerged the formulation of a new critical paradigm in the curriculum field: neosystemic curriculum metatheory, it could be stated that education research is a new knowledge factor when making the implementation of subsequent research projects a sharper source of questioning the object. Some education sciences were questioned, beyond the ideological criticism thought possible, from an epistemological learning that elucidated a horizon of a greater object understanding, new categories of analysis were formulated, a new classification of critical curriculum in the West was proposed, and the action research method was redefined.